TechTip : Infotoons - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
L'Agricultural Resource Council (ARC) a trouvé une manière ingénieuse de contourner les difficultés de lecture de ses clients, baptisée " Infotoons " (" information cartoons " ou bandes dessinées informative